2021
DOI: 10.1158/1535-7163.mct-21-0361
|View full text |Cite
|
Sign up to set email alerts
|

Vimseltinib: A Precision CSF1R Therapy for Tenosynovial Giant Cell Tumors and Diseases Promoted by Macrophages

Abstract: are employees and shareholders of Deciphera Pharmaceuticals. D.L.F. is founder of Deciphera Pharmaceuticals and a member of its scientific advisory board. S.C.W. is a former employee of Deciphera Pharmaceuticals. B.W. and L.D. are investigators on the clinical study of vimseltinib. B.W. has received financial or material support from GlaxoSmithKline, Lilly, Adaptimmune, Advenchen Laboratories, Daiichi Sankyo, Deciphera, Agenus, and Novartis. B.W. is a paid consultant for Deciphera, Adaptimmune, Springworks, Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Nilotinib's patent expires in 2023 in both the United States and the European Union, and could be a possible solution as a low-cost off-label drug [37]. More recently, new CSF1R inhibitors have been developed and investigated, such as cabiralizumab and vimseltinib [22,38]. Apparently, cabaralizumab is not developed further whereas vimseltinib is currently being explored in a phase III registration study (MOTION) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Nilotinib's patent expires in 2023 in both the United States and the European Union, and could be a possible solution as a low-cost off-label drug [37]. More recently, new CSF1R inhibitors have been developed and investigated, such as cabiralizumab and vimseltinib [22,38]. Apparently, cabaralizumab is not developed further whereas vimseltinib is currently being explored in a phase III registration study (MOTION) [39].…”
Section: Discussionmentioning
confidence: 99%
“…These cells attract and stimulate a large population of bystander macrophages (3). A number of studies have shown that these tumors react to inhibition of the CSF1 pathway (6)(7)(8)(9)(10)(11)(12)(13)24). To better understand the "landscaping effect" caused by the neoplastic cells on the tumor micro environment we used scRNA-seq and long read RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggested that the chemoattractant and proliferative effect of CSF1 on bystander macrophages could be inhibited by drugs that interfered with the CSF1 pathway. Studies using monoclonal antibodies and small molecule inhibitors for the CSF1 pathway have shown a significant clinical effect (6)(7)(8)(9)(10)(11)(12)(13) and a decrease in tumor size as seen by an imaging measurement specifically designed for TGCT (14). It was hypothesized that the CSF1-expressing neoplastic cells might be activated through an autocrine loop by CSF1R expressed on their surface (3).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical activity of vimseltinib alone, or in combination with anti-PD1 mAb, was shown, together with Mф depletion and suppression of CSF1R kinase activity. Moreover, in the phase I/II trial (NCT03069469), vimseltinib showed a tolerable safety profile, and biological as well as clinical activity in 13/29 patients [ 36 ].…”
Section: Targeting Immune System In Cancermentioning
confidence: 99%